Genome-Wide Association Study of 2,093 Cases With Idiopathic Polyneuropathy and 445,256 Controls Identifies First Susceptibility Loci - Winsvold, Bendik S.; Kitsos, Ioannis; Thomas, Laurent F.; Skogholt, Anne Heidi; Gabrielsen, Maiken E.; Zwart, John-Anker; Nilsen, Kristian Bernhard (Frontiers in Neurology, 2021)
Background: About one third of patients with chronic polyneuropathy have no obvious underlying etiology and are classified as having idiopathic polyneuropathy. The lack of knowledge about pathomechanisms and predisposing factors limits the development of effective prevention and treatment for these patients. We report the first genome-wide association study (GWAS) of idiopathic polyneuropathy. Methods: Cases with idiopathic polyneuropathy and healthy controls were identified by linkage to hospital records. We performed genome-wide association studies using genetic data from two large population-based health studies, the Trøndelag Health Study (HUNT, 1,147 cases and 62,204 controls) and UK Biobank (UKB, 946 cases and 383,052 controls). In a two-stage analysis design, we first treated HUNT as a discovery cohort and UK Biobank as a replication cohort. Secondly, we combined the two studies in a meta-analysis. Downstream analyses included genetic correlation to other traits and diseases. We specifically examined previously reported risk loci, and genes known to cause hereditary polyneuropathy. Results: No replicable risk loci were identified in the discovery-replication stage, in line with the limited predicted power of this approach. When combined in a meta-analysis, two independent loci reached statistical significance (rs7294354 in B4GALNT3, P-value 4.51 x 10-8) and (rs147738081 near NR5A2, P-value 4.75 x 10-8). Idiopathic polyneuropathy genetically correlated with several anthropometric measures, most pronounced for height, and with several pain-related traits. Conclusions: In this first GWAS of idiopathic polyneuropathy we identify two risk-loci that indicate possible pathogenetic mechanisms. Future collaborative efforts are needed to replicate and expand on these findings.